Increased intracranial pressure in severe traumatic axonal injury patients - A retrospective single-center study - Westerberg, Gustaf; Hossain, Iftakher; Drake, Mattias; Tsitsopoulos, Parmenion P.; Marklund, Niklas (Elsevier, 2026)
Introduction: Traumatic axonal injury (TAI), often caused by rapid rotational forces and high-energy accidents, is common in severe traumatic brain injury (sTBI). The intracranial pressure (ICP) dynamics are often unpredictable, and the need for ICP monitoring remains debated.
Research question: What is the incidence of ICP elevation in patients with TAI, and how often is escalated ICP-lowering treatment required?
Material and methods: Retrospectively, sTBI patients treated between 2007 and 2022 with TAI lesions at the grey–white matter interface, corpus callosum, deep central structures, and/or brainstem, on magnetic resonance imaging (MRI) were included. Patients with ICP elevation despite baseline management were treated according to the Lund Concept, including beta-blockers, clonidine, and albumin. Decompressive craniectomy (DC) or high-dose barbiturate infusion was reserved for refractory ICP elevation.
Results: Thirty-one TAI patients (15 women and 16 men) presented with a median Glasgow Coma Scale motor score of 2 (range 1–6). All patients had TAI lesion in the grey-white interface, 27 patients also in the corpus callosum, and 16 patients had brainstem lesions. Elevated ICP was observed in 16 patients (52 %), of whom 4/16 (25 %) received either DC (n = 2), high-dose barbiturates (n = 1) or both (n = 1).
Discussion and conclusion: The risk of increased ICP in TAI patients has been debated. Our present results, showing that 52 % of TAI patients experienced elevated ICP requiring escalated ICP-lowering strategies, argue that ICP monitoring is required in TAI. The impact of increased ICP on outcome following TAI should be explored in future studies.